Microwave-assisted multicomponent synthesis of antiproliferative 2, 4-dimethoxy-tetrahydropyrimido[4, 5-b]quinolin-6(7H)-ones. Issue 47 (25th October 2022) - Patel, Subham G.; González-Bakker, Aday; Vala, Ruturajsinh M.; Patel, Paras J.; Puerta, Adrián; Malik, Apoorva; Sharma, Rakesh K.; Padrón, José M.; Patel, Hitendra M.
Abstract : Herein, we demonstrate a simple, rapid and green synthesis of 2, 4-dimethoxy-THPQs under microwave irradiation and their antiproliferative activity, in silico ADMET and drug-likeness studies were carried out. Abstract : In this study, we demonstrate a simple, highly efficient, rapid and convenient series of 2, 4-dimethoxy-tetrahydropyrimido[4, 5- b ]quinolin-6(7 H )-ones 4a–v . Microwave irradiation facilitates the one-pot multicomponent reaction of different aromatic aldehydes, 6-amino-2, 4-dimethoxypyrimidine and dimedone using glacial acetic acid. Metal-free multicomponent synthesis, shorter reaction time, higher product yield, easy product purification without column chromatography and outstanding green credential parameters are the key features of this protocol. We analysed 4a–v against six human tumour cell lines for antiproliferative activity. 4h, 4o, 4q and 4v show good antiproliferative activity with a good in silico ADMET profile. Furthermore, 4h, 4o, 4q and 4v also show drug-likeness properties by obeying drug-like filters.